EVALUATION AND ANALYSIS OF DEBIT AND PRESSURE ON NETWORK DISTRIBUTION PDAM TIRTA KAHAYAN KOTA PALANGKA RAYA - I Made Alit Widnyana (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
PDAM Tirta Kahayan of Palangkaraya city has a technical problem regarding with inadequate service standard (coverage level). As a result from the direct observations at the service area of PDAM Tirta Kahayan of Palangka Raya city, there were numerous public complaints related to PDAM services, especially the issue on fees, debit and distributed water pressure. Lossing water in PDAM Palangka Raya City ranges from 23% -35%. The aims of this study is to identify the condition of the pipeline distribution network of PDAM Tirta Kahayan in Palangka Raya City, to evaluate the debit distribution patterns and pressure on pipeline network of PDAM Tirta Kahayan Palangka Raya City by simulating the Epanet 2.0 program and to compare the simulation results with the exiting conditions, moreover to analyze the improvement alternatives debit and pressure on distribution piping networks. Based on the results of the simulation of Epanet 2.0 program there are still some locations that have debits and flow rates below 0.3 LPS. This is due to differences in elevation, the distance which is getting much more apart from the service source and mismatching of the pipe dimension. The improvement alternatives that have been made are by installing booster pumps in several locations that aim to increase the flow and flow velocity, continuous reservoir filling and regulation of distribution pump operation; therefore the water pressure is always maintained.